(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Caffeine is known to confer neuro-protection via A1 and A2A adenosine receptor antagonism in which adenosine neuro-modulates excitotoxic release of glutamate. Currently, it is unclear whether caffeine modulates inflammation in ischaemic stroke model. The present study examined effects of caffeine following ischaemia-reperfusion injury on neuro-inflammatory tumour necrosis alpha (TNF-α), lactate dehydrogenase (LDH), as well as effect of caffeine against brain ischaemic damage on histology. Thirty three adult male Wistar rats (180-300 g) were used in this study. They were randomly divided into four groups (n=5 each): Group I (Control) that received neither the operation nor any treatment; Group II (Sham/Water) received a pseudo-ischaemic-reperfusion and 1ml water for injection; Group III (BCCO/Water) that received complete bilateral common carotid occlusion (BCCO) and 1ml water for injection; Group IV (BCCO/Caffeine) that received complete BCCO and caffeine solution intraperitoneally at a dose of 50% LD50 value (144mg/kg); and thirteen rats were used for LD50 assessment. Sensory and motor functions significantly (p<0.05) decreased in the rat following ischaemia-reperfusion injury when compared to pre-injury state on Garcia neurological score. Caffeine reduced brain ischaemic injury and significantly reduced (p<0.05) TNF-α activity. While no significant effects (p>0.05) of caffeine was observed on LDH activity. This study has shown neuro-protective roles of caffeine against ischaemia-reperfusion damage to brain tissue, inflammatory TNF-α activity, but not on LDH activity